Le traitement de la virginité chez les migrants pentecôtistes à Bruxelles - Maïté Maskens (L'Espace Politique)
This text frames the particular sexual behaviors of migrant African and Latin Americans who are members of the Pentecostal community in Brussels. This identification allows religious believers to see themselves as the last bastion of morality in a Europe viewed as "decadent", the domain of sexual practices that are then the object of profound criticism. So setting the scene, faithful Pentecostals construct their differences in the register of sexuality. Attempting to make order out of transformation and pursuing an ideal of distinction, these religious actors (mainly women) need therefore not be like the locals, whom pastors have denounced for their permissiveness and "lax" sexual practices (partially legal prostitution, lack of public "decency", legality of same-sex marriage, pornography accessible to young people, STD prevention campaigns in the schools...). After having reviewed the main arguments about sexuality offered by the pastoral voice and the official religious record, this article intends to analyze the creativity and inventiveness exhibited by believers to live their religious norms, and more particularly how they re-appropriate the norm of premarital chastity. In this context, we see how young girls in the congregation constitute a “capital of purity” in numerous churches and are thus the primary targets of Sunday sermons based on a logic that associates femininity with guilty “temptation.”